Can Artificial Intelligence (AI) like QuillBot AI Assist Students’ Writing Skills? Assisting Learning to Write Texts using AI - Riza Laras Amyatun; Adhan Kholis (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
At present, it is undeniable that the influence of Artificial Intelligence (AI) in learning English is increasing. AI helps students develop English sentences. This study aims to assist eleventh-grade students’ skills in creating hortatory exposition texts using QuillBot AI. It was Classroom Action Research (CAR) using the Kemmis, McTaggart, and Nixon paradigm conducted in two cycles, each consisting of three meetings. Each cycle included planning, acting, observing, and reflecting. The participants of this study were students from XI IPA 2A, consisting of 20 students. The data collection technique employed was a test. Before giving treatment, the students did a pre-test in the form of a writing test. Then, the researcher taught the students using Quillbot AI in several meetings. A paired sample t-test was administered using the SPSS version 25 to analyze the obtained data. The findings revealed that using QuillBot AI in the writing class considerably improved students’ writing skills. It was demonstrated by the results of the students’ writing test scores. In the pre-test, the students’ mean score was 53.55. Then, after utilizing QuillBot AI, the students’ mean post-test score was 78.90. In addition, the significance of the difference could also be seen in the acquisition of a sig. (2-tailed) value of 0.000, which meant it was smaller than 0.05. Based on the statistics presented, Ho was refused, and Ha was approved, indicating that QuillBot AI’s usage impacted the students’ ability to create hortatory exposition texts.